Accounting Information System Quality and Islamic Work Ethic as Determinants of Financial Employee Performance: Evidence from SAKTI Implementation at a State Islamic University - Novri Rahmat; Sandra Ayu; Rahmatika; Novia Citra Dewi (BAITUL MAAL : Journal of Sharia Economics, 2026)
The digital transformation of government financial management makes the quality of information systems a critical prerequisite for the accuracy, speed, and accountability of employees’ work. However, in religious-based public institutions, performance is determined not only by technological capacity but also by ethical orientations that shape discipline, trustworthiness, and work responsibility. This study analyzes the influence of the quality of the accounting information system and the Islamic work ethic on the performance of financial staff at Imam Bonjol State Islamic University, Padang. The study employs an explanatory quantitative design using a census approach involving all 35 financial staff members. Data were collected via a questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3.0. The results show that the quality of the accounting information system has a positive and significant effect on employee performance (β = 0.309; t = 2.167; p = 0.031), while the Islamic work ethic also has a positive and significant effect (β = 0.482; t = 4.153; p < 0.001). These two constructs explain 38.5% of the variation in employee performance. These findings indicate that improving performance in financial units requires a dual intervention: strengthening the reliability and usefulness of the SAKTI system and institutionalizing the values of trustworthiness, discipline, professionalism, and service orientation. The contribution of this study lies in integrating the perspectives of information system success and the Islamic work ethic to explain employee performance in the context of financial management at state-run religious universities.